Psychological antecedents of overuse injuries in swedish elite floorball players - Tranaeus, U.; Johnson, U.; Engström, B.; Skillgate, E.; Werner, S. (Athletic Insight Journal, 2014)
The epidemiology of sport injuries is well documented and the injuries can be divided into either traumatic or overuse injuries. So far, most research aiming to predict and prevent sport injures has focused on physical factors and traumatic sport injuries. The aim of this study was to identify psychological factors preceding overuse injuries. Eleven senior elite floorball players (men: n=9, women: n=2) were interviewed regarding their experiences of potentially stressful events before the onset of an overuse injury. Based on a thematic content analysis, five core themes were developed: history of stressors, person factors, psycho-physiological factors, psychosocial factors and ineffective coping. The results are discussed in the context of related research concerning subthemes and themes, such as stress, motivation, pain and social support; finally, recommendations are given for athletes and coaches. A working model is also suggested for future research.